PERENCANAAN DAN PERANCANGAN FASILITAS PENUNJANG PARIWISATA DI KAWASAN DESA WISATA PENGLIPURAN – BANGLI: Bahasa Indonesia - PURNAWAN, I wayan sudita purnawan; Parwata, I Wayan; Widanan, I Wayan; Putri, Ni Putu Ratih Pradnyaswari Anasta; Narayana, Kadek Putra Santika (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2025)
The increase in the number of tourists in the Penglipuran Tourism Village, Bali, has given rise to various problems such as a lack of supporting facilities and the conversion of traditional houses. This research aims to design supporting facilities that suit village characteristics and tourist needs, as well as preserving the environment and local culture. Through literature and field studies, this research identifies the main problems and proposes an eco-friendly architecture design concept that combines traditional Balinese architecture with modern technology. It is hoped that the results of this research can contribute to the development of sustainable tourism in the Penglipuran Tourism Village